A key to the Australian Sarcophagidae (Diptera) with special emphasis on Sarcophaga (sensu lato) - Meiklejohn, Kelly A; Dowton, Mark; Pape, Thomas; Wallman, James F (Zootaxa, 2013)
The Australian Sarcophagidae (Diptera) currently comprise 84 species, classified into ten genera from the subfamilies Miltogramminae and Sarcophaginae. A key is provided to the Australian sarcophagids, allowing for separation into sub-families and genera, along with the identification of all species of Sarcophaga (sensu lato). A comprehensive database of illustrations and photographs of male terminalia, as well as updated biological information, is given for each species of Sarcophaga s.l.